Peningkatan Kualitas Hidup Melalui Senam Lansia Dalam Membantu Mengurangi Risiko Penyakit Kardiovaskular Dan Meningkatkan Stamina - Ariyanti, Sri; Anggeraeni, Anggeraeni; Vandika, Arnes Yuli (Sahabat Sosial: Jurnal Pengabdian Masyarakat, 2025)
Various strategies have been attempted to improve the health and nutritional status of the elderly. One of them is through physical activity and sports that are appropriate to the physical condition of the elderly and are carried out regularly. The purpose of Community Service is to Increase Physical Strength and Flexibility Through light and measured exercise movements, the elderly can increase their muscle strength and joint flexibility. This helps prevent the risk of falls, maintain mobility, and improve posture. The method used in Community Service activities is the Implementation Method of this Community Service Activity is carried out through elderly gymnastics to help reduce the risk of cardiovascular disease and increase stamina, counseling, socialization, and coaching programs on Health in the community and training community elements to implement a healthy lifestyle. The results of this Community Service activity show that there is an increase in the quality of life of the elderly and also understanding its benefits for the health of the elderly. The conclusion is that this Elderly Gymnastics Program is to increase the enthusiasm of residents, especially the elderly, in maintaining health due to the problems of physical and mental health of the elderly who often experience problems.